VD_FINDINFO HC / 2013 / 45 vom 6. Dezember 2012 - VD Tribunal cantonal (2012)
RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL, INDEMNITÉ ÉQUITABLE, JUSTE MOTIF | 337 CO, 337c al. 3 CO, 337c CO, 316 al. 1 CPC (CH), 316 al. 3 CPC (CH)